A Stable Three‐Dimensional Porous Carbon as a High‐Performance Anode Material for Lithium, Sodium, and Potassium Ion Batteries. Issue 9 (14th July 2022) - Younis, Umer; Qayyum, Fizzah; Muhammad, Imran; Yaseen, Muhammad; Sun, Qiang
Abstract: Extensive efforts are devoted to the design of new carbon materials with improved specific capacity for metal ion batteries (MIBs). One of the effective strategies for such material design is to change the structural unit. Recently, tetracene‐based nanoribbons have been synthesized (Chem. Eur. J. 2019, 25, 12074), which can be used as a basic building block to design a 3D porous TC60 as demonstrated in this work. Based on first‐principles calculations, it is found that the 3D‐TC60 shows high dynamical and thermal stability. Furthermore, the 3D‐TC60 with its unique porosity and various adsorption sites can work as a high‐performance anode material for Li, Na, and K‐ion batteries with high specific capacity of 706, 706, 466 mAhg −1 ; low diffusion barrier of 0.25, 0.11, 0.08 eV; small volume change of 0.88, 1.96, 2.94%; and average voltage of 0.19, 0.24, 0.50 V, respectively. These intriguing findings suggest the promising prospect of tetracene based materials for battery technology. Abstract : Design of tetracene nanoribbon‐based 3D porous carbon as a universal anode material for Li, Na, and K‐ion batteries with high performance Low volume expansion of 0.88/1.96/2.94%